(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article examines the scientific and theoretical foundations of forming social responsibility in the educational process. The concept of social responsibility is analyzed from philosophical, pedagogical, and psychological perspectives, and its role in personal development is substantiated. The study explores the possibilities of the educational process, its content, forms, and methods in developing social responsibility among students. Particular attention is paid to modern educational paradigms, competency-based and learner-centered approaches. The findings of the study contribute to improving the effectiveness of educational and upbringing activities in educational institutions.